2020
DOI: 10.17759/sps.2020110103
|View full text |Cite
|
Sign up to set email alerts
|

Internet addiction and addiction to computer games in the work of Russian psychologists

Abstract: Objectives. This literary review is devoted to domestic research in the field of psychology of Internet addiction and addiction to computer games. Background. The popularity of topics related to Internet technologies is explained by their novelty, great dynamism and poorly studied, which causes social anxiety, catalyzing the activity of scientists in this area. In addition, one can note the high rate of spread of cyberdictions, due to which some authors are in a hurry to call them a threat to society. The stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 22 publications
0
0
0
2
Order By: Relevance
“…Recent research has also delved into the personal determinants of online behavior. Studies have shown that both individual characteristics and elements of the value-semantic sphere are linked to problematic Internet use, online presence parameters, communication patterns, and self-presentation [30,2,31,32]. Regarding the association with DRD2 gene polymorphisms, it is noteworthy that statistically significant effects were observed primarily in relation to the active "destructive" digital behavior form.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has also delved into the personal determinants of online behavior. Studies have shown that both individual characteristics and elements of the value-semantic sphere are linked to problematic Internet use, online presence parameters, communication patterns, and self-presentation [30,2,31,32]. Regarding the association with DRD2 gene polymorphisms, it is noteworthy that statistically significant effects were observed primarily in relation to the active "destructive" digital behavior form.…”
Section: Discussionmentioning
confidence: 99%
“…Объектом исследования была случайная выборка 3074 подростков 11-19 лет (46,1% мальчиков и 53,9% девочек) -учащихся 10 общеобразовательных учебных заведений 5 районов Красноярскакрупного промышленного и административного центра Красноярского края. Медиана возраста испытуемых составила 14 (13)(14)(15)(16) лет, подавляющее большинство (99,4%) из них находились в возрасте 12-18 лет. Младшие подростки (11-14 лет) составили 52,0%, старшие (15-19 лет) -48,0%.…”
Section: материалы и методыunclassified
“…В настоящее время существует консенсус в отношении диагностических критериев, позволяющий четко отграничить патологическую составляющую аддикции от нормального повседневного использования интернета подростками: клинический диагноз PSMU, как и генерализованная Materials and methods. After the procedures of direct and reverse translation of the questionnaire, the psychometric validation of the test was carried out on a Russian-speaking sample of 3074 adolescents aged 11-19 years (46.1% of boys and 53.9% of girls, median age 14 (13)(14)(15)(16)) years) -students of 10 educational institutions in Krasnoyarsk. The external validity of the SMDS-RU questionnaire was assessed using the following methods: Chen Internet Addiction Scale (CIAS) -to assess the presence of Internet addicted behavior; the Strengths and Challenges Questionnaire (SDQ) -to analyze the mental health of the subjects.…”
Section: Introductionunclassified
“…Компаративный Например, Н. В. Кочетков указывает на границы распространенности форм технологической зависимости в регионах России от 4,3 до 22,8 % [11]. Подобные данные представлены также в трудах М. А. Южанина, подтверждающего, что в 2020 г.…”
Section: обзор литературыunclassified